The effect of ICT on trade: Does product complexity matter?. (August 2019) - Rodríguez-Crespo, Ernesto; Martínez-Zarzoso, Inmaculada
Highlights: We test ICT effects on bilateral trade segmenting by income and product complexity. We employ Internet usage as a proxy for Information and Communication Technologies. We estimate a structural gravity model using PPML for 120 countries during 2000–2014. We find that countries with similar product complexity and ICT levels trade more. Abstract: We use a gravity model of trade to investigate the effect of internet use on aggregate trade flows. We apply a structural gravity model using up-to-date PPML estimation techniques to a sample of bilateral exports of 120 countries over the period 2000–2014. In contrast to previous studies, we segment countries according to their degree of product complexity and estimate the model for each segment. The results show that internet use increases trade, and the segmentation by product complexity is more sensitive to internet use than segmenting by level of income. The main results also indicate that countries trade more if similar levels of ICT use are coupled with similar degrees of product complexity in the trading countries.